Process Based Approach towards Students’ Creativity in Writing English Paragraph - Siti Syafi’atul Qomariyah; Dira Permana (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
The research entitled “Process based Approach towards Students’ English Paragraph Writing Ability” aims to discover whether or not Process based Approach is effective or not towards students’ English paragraph writing ability. This was a queasy-experimental research with pretest-posttest control group design. The population of the study was the fourth semester students of Writing subject of English Department at Language and Art Education Faculty of IKIP Mataram in the academic year of 2016/2017. Samples of the study were IV-E and IV-F taken through cluster random sampling technique. To determine the experimental and control class, lottery was used. Instrument of the research was paragraph writing test. Techniques of analyzing data were descriptive and inferential statistic analysis. Data of samples were in normal distribution since the value of sig (081) was higher than the value of alpha (0.05). Data of samples were also homogeneous as the value of sig (012) was higher than the value of alpha (0.05). Based on the result of t-test of two-tailed independent samples, it was found that the value of sig (196) was lower than the value of alpha at the level of significance (0.05). It means that Process based Approach was not effective towards students’ English paragraph writing ability.